PENGARUH MEDIA PEMBELAJARAN GAME EDUKASI TERHADAP KEMAMPUAN SISWA SEKOLAH DASAR DALAM BERHITUNG - Rendi Marlianda; Aprimadedi; Titus Nugroho (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
In light of the evolving times, a variety of new types of games have emerged, especially with the rapid advancement of technology, which has significantly influenced the development of new game genres. Besides being created for enjoyment, games can also be designed for educational purposes with specific objectives as educational tools. Educational games have proven to increase students' interest in learning, making them a revolutionary step in enjoyable learning for students. This research is a quantitative study with an experimental approach using a two-group pretest-posttest design. Quantitative research deals with data and numbers, starting from data collection, interpretation of the data, and presenting the final results in numerical form. Quantitative research is also a process that generates numerical data and analyzes it using statistics. This research design aims to ensure that the research process is directed and follows the proper procedures.Based on the t-test result of 7.622, which is greater than the t-table value of 2.728 (7.622 > 2.728), it means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. The acceptance of Ha indicates that there is a difference in the average scores of multiple-choice questions between the posttest and the pretest. The positive t-test value shows that the average posttest results are higher than the average pretest results. Therefore, the Math Educational Game has an impact on the counting ability of third-grade students. Similarly, for the experimental class, the t-test result of 9.354 is greater than the t-table value of 2.728 (9.354 > 2.728), which means that Ha is accepted and Ho is rejected. The acceptance of Ha indicates that there is a difference in the average scores of multiple-choice questions between the posttest and the pretest. The positive t-test value shows that the average posttest results are higher than the average pretest results. Thus, the Math Educational Game affects the counting ability of third-grade students.